Context-Informed Perspectives of Child Risk and Protection in Israel - Roer-Strier, Dorit; Nadan, Yochay (Child Maltreatment, Contemporary Issues in Research and Policy, 2020)
XIV, 331 p. 11 illus., 4 illus. in color.